Incidencia del uso masivo de internet en la formación académica de los estudiantes del séptimo año de la escuela “Luis Pasteur” de la parroquia Santiago del cantón Loja, provincia de Loja, periodo 2014-2015 - Viñamagua Japón, Karina Cecibel (2016)
This thesis called “INCIDENCIA DEL USO MASIVO DE INTERNET EN LA FORMACIÓN ACADÉMICA DE LOS ESTUDIANTES DEL SÉPTIMO AÑO DE LA ESCUELA “LUIS PASTEUR” DE LA PARROQUIA SANTIAGO DEL CANTÓN LOJA, PROVINCIA DE LOJA, PERIODO 2014-2015”. PROPUESTA ALTERNATIVA, the central problem of the research is to determine the influence of the mass use of the internet in the seventh year student’s basic school education Luis Pasteur Santiago parish. For the development of this research work using various methods as: scientific, inductive, deductive, descriptive statistics; same techniques and tools as well as the survey of students and teachers of the institution With the results obtained come to the following conclusions : students of the seventh year of basic school education " Louis Pasteur " use the internet continuously for their research work ; it is also used as a way of distraction : the use of social networks such as e- mail , Facebook , listening to music or watching videos ; or just out of curiosity ; As far as teachers are recommended to encourage students through lectures on proper and positive use of the Internet , to assist the development and academic performance of each . Also to demand parameters for research topics such as: the source, author's name, and research analysis, thus developing skills, study skills that will serve students for personal, academic and professional life.